Evaluation of'the Buddy Study', a peer support program for second victims in healthcare: a survey in two Danish hospital departments - Katja Schrøder; Tine Bovil; Jan Stener Jørgensen; Charlotte Abrahamsen (BMC, 2022)
Abstract Background Healthcare professionals involved in adverse events may suffer severe physical and emotional distress in the aftermath. Adequate support is critical to an overall culture of safety for any healthcare institution. This study evaluates a formalised peer support program, 'the Buddy Study', in two Danish university hospital departments. The program consists of a 2-h seminar about second victims and self-selected buddies to provide peer support after adverse events. Methods The study design involved a cross-sectional survey comprised of two close-ended questionnaires evaluating the Buddy Study seminar (Q1) and the Buddy Study program (Q2), along with two open-ended questions and three individual interviews for more elaborate answers. Results Out of the 250 HCPs employed in both departments, 191 midwives, physicians, and nursing assistants completed Q1 and 156 completed Q2. The seminars were evaluated positively; 91.6% were satisfied with the overall content of the seminar, and 69.1% agreed that insight into how other people may react to adverse events has helped them contain their own reactions or emotions. Assessments of having the Buddy Study program in the department or using or being used as a buddy were more diverse, yet overall positive. Three benefits of the program were identified: the program i) has encouraged an open and compassionate culture; ii) has caused attentiveness to the wellbeing of colleagues; and iii) the self-selected buddy relationship has created a safe space for sharing. Additionally, three challenges or shortcomings were identified: i) although peer support is valuable, it should not stand alone; ii) informal peer support is already in place, hence making a formalised system redundant; and iii) the buddy system requires continuous maintenance and visibility. Conclusions The overall evaluation of the Buddy Study program was positive, suggesting that this type of formalised peer support may contribute to a rapid and accessible second-victim support program in healthcare institutions. A key principle for the Buddy Study program is that relationships are crucial, and all buddy relationships are based on self-selection. This seems to offer a safe space for health care professionals to share emotional vulnerability and professional insecurity after an adverse event.